センヨウ カンソクセン ニヨル カイヨウ カンソク ニ カンスル ケンキュウ ショウシュウカイ ソノ2 ホウコク - 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Fukuchi, Mitsuo (2004)
P(論文) 「専用観測船による海洋観測に関する研究小集会(その2)」を,国立極地研究所講義室において2003年8月5日に開催した.参加者は23名であった.出席した研究者から,第43次及び第44次日本南極地域観測隊の海洋研究航海で実施された研究成果の現状と今後投稿予定の論文表題についての報告があった.これら関連論文をどのように発表してゆくかを議論し,時系列観測で得られた成果をテーマに科学雑誌の特集号としたいという合意が得られた.これらの論文内容を,日豪セミナーでオーストラリア側研究者と議論した後,日豪共同で特集号とするか否かを打ち合わせることとした. A Workshop "Marine Science Program using a Charter Research Vessel-Part II" was held on 5th August 2003 at the National Institute of Polar Research (NIPR), Tokyo, with 23 participants. The present status of scientific results, which were collected during the 43rd and 44th Japanese Antarctic Research Expedition (JARE-43 and JARE-44) Marine Science Cruises, was reported. Tentative titles of research papers, which will be submitted to scientific journals, were suggested. Participants discussed the publication of research papers and agreed with submission to a special volume of an international scientific journal, of which the main scope will be time-serial observations. After discussion with an Australian scientists in the end of August 2003, the special volume will be compiled by Japanese and Australian guest editors. departmental bulletin paper